MARINE AUDIT AS AN EARLY DETECTION TOOL FOR CONFLICTS AND ZONING VIOLATIONS IN INDONESIAN COASTAL AREAS - Wahyudin, Yudi (Politeknik Kelautan dan Perikanan Dumai, 2025)
Management of spatial marine in Indonesia faces serious challenges due to increasing intensity of utilization, overlapping functions between sectors, and weak supervision and compliance with coastal zoning. These conditions often trigger conflicts between coastal communities, business actors, and the government, and cause degradation of marine ecosystems. This study aims to develop a marine space audit model as an instrument for early detection of conflicts, zoning violations, and socio-ecological non-conformities. The methods used are literature studies and expert judgment approaches based on direct involvement in resolving environmental disputes in coastal areas. The resulting audit model consists of three main components: (1) Conflict and Risk Zones (weighting 0.40), (2) Legality and Compliance (weighting 0.35), and (3) Social-Ecological System Suitability (weighting 0.25). Each component consists of several indicators and sub-indicators that are assessed using a five-level risk scale: Very High, High, Medium, Low, and Very Low. The total audit score is calculated by averaging the sub-indicator scores and weighting between components. The results of the study indicate that this model can help identify potential conflicts and violations early on and provide an argumentative basis for more responsive and equitable policy interventions. Marine space audits also open opportunities for participatory and adaptive monitoring in coastal area management. The main recommendations of this study include integrating audits into zoning policies, strengthening institutional capacity, and developing a digital system for indicator-based monitoring.